KELSEN AND SCHOLTEN ON REASON AND EMOTION IN SOLVING CASES (Revista Paradigma, 2016)
This paper compares two accounts of legal methodology: Kelsen’s and Scholten’s. It focuses on the relationship of the diferent psychic faculties (specially reason and emotion) in solving legal cases.